A New Model for Pharmacies? Insights From a Quantitative Study Regarding the Public's Perceptions - V Policarpo; S Romano; JHC António; TS Correia; S Costa (Formifarma, LDA., 2019)
Background Worldwide community pharmacies are shifting their role in the healthcare system from simple medication dispensers to health care providers. High levels of satisfaction with pharmacy services were found in previous studies. This study has two main goals. The primary goal is to describe the levels of satisfaction and knowledge regarding pharmacy services in Portugal. The secondary goal is to explore the perceptions and the utilization of pharmacy services by the Portuguese. This statement includes exploring the impact of a set of variables on both perceptions and uses of pharmacies in regard to services that are currently offered as well as to new services that may be provided in the future. Methods A face-to-face survey of closed-ended questions was applied to a nationwide representative sample of the Portuguese population in September 2015. The sample was weighted based on population distribution across regions, habitat, age and gender. Data analysis comprises descriptive statistics and Multiple Correspondence Analysis to explore different typologies of respondent's orientation toward community pharmacy. Results A total of 1114 interviews comprised the study. Of the respondents, 36% used the pharmacy as a first resource when seeking to treat a minor ailment, and 54% reported that they use the pharmacy as a first resource when seeking answers about medicines. Of those who visited their pharmacy at least once in the previous year, 94% were either globally satisfied or very satisfied. The level of acknowledgement of pharmacy services' was also high among the Portuguese. Of the participants, 29% considered there could be more services available in pharmacies that are currently provided by other health care facilities. The construction of a typology of orientations towards community pharmacy practice resulted in three outcome groups: "Motivated" (63%), those with a connection to a pharmacy; "Settled" (23%), mainly those who had a pharmacy nearby; and "Demobilised" (14%), those who are weakly tied to a pharmacy. Conclusions The vast majority of the Portuguese population has a strong positive attitude towards their community pharmacy, as expressed by the high levels of satisfaction with, and positive evaluation of, the pharmacy's services. Published in: BMC Health Serv Res. 2019;19:186.